Pelvic Congestion Syndrome: current approach and future diagnostic perspectives (Bangladesh Journal of Medical Science, 2021)
Objective: The aim of this review is to present the ways of approaching Pelvic Congestion Syndrome (PCS) and to emphasize on the current trends and problems of diagnosis.Background: PCS represents a cause of chronic pelvic pain, affecting mainly women and suspected frequently during pregnancies. It is underdiagnosed partly because patients do not tend to investigate their symptomatology, but also because of the invasive character of the golden standard procedure for diagnosis, venography. Treatment includes interventional, medical and surgical alternatives.Conclusions: Currently, ultrasound parameters are being assessed in order to replace venography, as it is usually performed in most patients in gynecology and most important it is non-invasive. Transvaginal approach, the use of Doppler mode and Valsalva maneuver, vein diameters can help orientate the diagnosis, pointing that US should have the potential to be used both as a screening test and diagnostic procedure in the future.Bangladesh Journal of Medical Science Vol.20(2) 2021 p.258-262